Training on the Utilization of AI to Create Questions for Teachers in Muara Gembong District Schools - Soeprijanto, Soeprijanto; Prihantoro, Constantinus Rudy; Nursyahied, Imam; Wahyu Nugroho, Setiadi Dwi; Salsabina, Desti Aulia; Fadillah, Shinta (Abdi Masyarakat, 2025)
The development of artificial intelligence (AI) technology has opened up significant opportunities to enhance efficiency and quality in education, including exam question creation. However, the use of AI by teachers in the Muara Gembong sub-district remains very limited due to a lack of understanding and technical skills. This community service activity aimed to improve teachers' competencies in utilizing AI-based applications such as ChatGPT, Quizizz, and Google Forms to develop exam questions more variably and efficiently.The implementation method included several stages: outreach, initial surveys, module development, hands-on training, as well as mentoring and evaluation. The activity involved 15 teachers from various educational levels in the area. Evaluation was conducted through pre-tests and post-tests to measure the improvement in participants' understanding and skills.The results showed an increase of 10 to 20 points for the majority of participants, reflecting the effectiveness of the module and materials in enhancing their understanding of AI-based question development. The decrease in the percentage of participants scoring below average (<70) from 100% to 70% is a positive initial indicator of improved teacher competency. Despite this significant improvement, 70% of participants still scored below 70. In addition, the training successfully fostered collaborative spirit among teachers in integrating technology into the learning process. This activity demonstrates that with appropriate training and sustained support, teachers in areas with limited access to technology can effectively adopt digital innovations.